THE SOCIAL STATUS OF HAJJ IN RURAL LAMPUNG - Lestari, Amilia; Kamaludin, Mohamad Imam; Wijayanto, Fery (Multazam : Jurnal Manajemen Haji dan Umrah, 2024)
This study examines the impact of performing the Hajj pilgrimage on an individual's social status in rural Lampung communities. The aim of this research is to analyze how the titles 'Haji' or 'Hajjah' influence social standing, religious leadership roles, and their relation to economic capacity. The research methods used are observation and interviews. The findings show that individuals who have completed the Hajj experience a significant rise in social status. The title "Haji" or "Hajjah" attached to their names adds prestige and respect within the community. Moreover, they are often entrusted with leading religious and social events and assume important roles in local religious leadership. The social status of Hajj is also reflected in changes in clothing style and other physical symbols, indicating a stronger religious commitment. The ability to perform Hajj is often associated with good economic standing, further reinforcing the positive perception of their financial status. Overall, the Hajj not only elevates social status but also fosters an increase in religious education within rural Lampung communities.